Functional and Economic Evaluations for Choosing Road Intersection Layout - Raffaele Mauro; Marco Cattani (Promet - Traffic&Transportation, 1970)
The road intersection design requires a choice among different layouts, for example signalized intersections or roundabouts. Generally, layouts which provide higher level of services are the most expensive ones. For this reason, the choice has to consider both fixed and variable costs, the latter consisting in the delays suffered by the drivers crossing the junction. The paper presents a procedure to compare different layouts, taking into account the costs of construction, management/maintenance and delays. The cost of delay is estimated with different traffic conditions, by the evaluation of the layout performance, in terms of delays at the approaches. With the example traffic conditions and parameters values considered in the paper, the compact roundabout turns out to be the layout with the least overall cost. The examples of sensitivity analyses are also provided to understand the cost dependence on the parameters used.